Emergence of Japanese encephalitis virus genotype V in the Republic of Korea - Grieco John; Lee Won-Ja; Klein Terry A; Kengluecha Ampornpan; Tippayachai Bousaraporn; Kim Heung-Chul; Takhampunya Ratree; Evans Brian P (Virology Journal, 2011)
Abstract Background Japanese encephalitis virus (JEV) genotype V reemerged in Asia (China) in 2009 after a 57-year hiatus from the continent, thereby emphasizing a need to increase regional surveillance efforts. Genotypic characterization was performed on 19 JEV-positive mosquito pools (18 pools of Culex tritaeniorhynchus and 1 pool of Cx. bitaeniorhynchus) from a total of 64 positive pools collected from geographically different locations throughout the Republic of Korea (ROK) during 2008 and 2010. Findings Two regions of the JEV genome were sequenced from 19 pools; the envelope gene and the nonstructural protein 5 (NS5)/3'-untranslated region (UTR). Eighteen pools of Culex tritaeniorhynchus and one pool of Cx. bitaeniorhynchus were positive for genotype I and genotype V, respectively. Sequence alignment of the complete E gene from Cx. bitaeniorhynchus showed high amino acid similarity (98.8%) to the Muar strain, characterized as the first report of genotype V, isolated from an encephalitis patient in Malaysia in 1952. Conclusion This study represents the first report of JEV genotype V in the ROK. The reemergence of genotype V in Asia (China and ROK) after more than a half-century and its discovery in Cx. bitaeniorhynchus, a mosquito species previously unknown to carry JEV in the ROK, emphasizes the need for enhanced JE surveillance to monitor the dynamics of JEV strains within the region. Future findings may have implications with regard to JEV vaccination/prevention strategies.